The impact of school trips in Bangkok, Thailand - Jin, Fan; Yordphol Tanaboriboon; Fukuda, Atsushi; Mori, Hiroshi; The Government of Australia (Bangkok : Asian Institute of Technology, 1991)
In Bangkok, traffic congestion h as been often described as being one of the serious problems, and has become almost a way of life. There are many factors contributing to traffic congestion in Bangkok. Among many causes of Bangkok's chronic traffic congestion, school trips also play a major role in contributing the severe traffic situation. This research study focuses on the impact of school trips in Bangkok . Travel time and volume counts surveys at three selected sites were conducted to confirm these impacts. Furthermore questionnaire surveys to the randomly selected schools were employed to reveal the characteristics of the school tiremakers and their families , the travel mode choice and the attitude towards school bus , etc. Results of the before and after studies which represented schools on holidays and in session revealed that travel time increased significantly at the 5 percent level at all survey sites and as well as for all survey periods. Travel time were increased significantly ranging from 21.23 percent to as high as 1830.21 percent. Moreover, traffic volumes were found to be significantly increased resulted from t h e effect of schooling . An increment of as high as 46.43 percent has noticed at one of the study sites. These results concluded that the traffic were adversely affected by school trips. Since more than half of school trip-makers are u sing private cars for school purpose, it is possible to reduce traffic demand for school trips if school bus system could be implemented. Furthermore , it was found t hat the number of willing users of school bus is quite substantial provided school buses could be standardized by the authority concerned. This information is helpful to t h e decision-maker for introducing standard school bus system in Bangkok to alleviate traffic congestion as well as to meet the school trip-makers' demand.
A thesis submitted in partial fulfillment of the requirements for the degree of Master of Engineering, School of Engineering and Technology
Thesis (M.Eng.) - Asian Institute of Technology, 1991
Keywords: Traffic flow -- Thailand -- Bangkok; School children -- Thailand -- Bangkok -- Transportation